Analysis of sensitive information leakage in functional genomics signal profiles through genomic deletions - Arif Harmanci (Nature Portfolio, 2018)
Functional genomics data from many studies are widely shared publicly for their value in biomedical and disease research. Here, the authors show sensitive information leakage is possible by analyzing functional genomics signal profiles, and develop an anonymization procedure for privacy protection.